PENGARUH METODE PEMBAYARAN DIGITAL, POTONGAN HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA PT ATEK SUKSES MANDIRI - Kuwangga, Henry; fitriano, Andre; Pangestu, Ivan; Nicholas, Gavriel; Pratiwi, Henny (Mount Hope Management International Journal, 2025)
This study was conducted to analyze how digital payment methods, discounts, and product quality influence purchasing decisions among consumers at PT. Kiat Atek Sukses Mandiri. Data was gathered through questionnaires distributed to an unspecified number of consumers from PT. Atek Sukses Mandiri's population, then processed and tested using SPSS 21 software. The hypothesis testing results indicate that all variables examined—digital payment methods, discounts, and product quality—have a positive and significant influence on purchasing decisions. This holds true both individually and simultaneously. The combined contribution of these three variables to purch|asing decisions is 60%, leaving the remaining 40% influenced by other factors not within the scope of this research. Among the three, product quality emerged as the most significantly influential factor, contributing 43.7% of the total observed influence.